Analisis Terhadap Kepastian Hukum Putusan Mahkamah Konstitusi Nomor 46PUU-VIII2010 Sebagai Bukti Dalam Penyelesaian Kasus Anak Diluar Nikah: Analisis Terhadap Kepastian Hukum Putusan Mahkamah Konstitusi Nomor 46PUU-VIII2010 Sebagai Bukti Dalam Penyelesaian Kasus Anak Diluar Nikah - Putra, Mahendita Galang Perdana Humaidi; Suhariningsih, Suhariningsih; Wisnuwardhani, Diah Aju (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to analyze the legal certainty of the Constitutional Court Decision Number 46/PUU-VIII/2010 regarding the legal status of children born out of wedlock. This decision regulates the recognition of rights for children born out of wedlock, who previously often did not receive adequate legal protection. The analysis is carried out by examining the implications of the decision on legal practices in Indonesia, including how the decision can serve as evidence in resolving disputes related to the legal status of children. Additionally, this research also examines the impact of the decision on the protection of children's rights, as well as the response of society and the government in supporting the implementation of the decision. The results of this analysis are expected to provide a better understanding of the role of the Constitutional Court in upholding legal certainty and the rights of children in the social and legal context of Indonesia. The method used in this research is a normative legal research method, which is applied to examine regulations related to the protection for children born out of wedlock under Constitutional Court Decision No. 46/PUU-VII/2010 is incomplete, as the decision requires DNA testing to establish paternity but lacks enforceable regulations to compel such testing. Despite its limitations, the decision reflects the state's effort to protect these children while encouraging compliance with marriage laws to create a more conducive legal environment.